2008
DOI: 10.2527/jas.2007-0267
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary phosphorus and calcium level, phytase supplementation, and ileal infusion of pectin on the chemical composition and carbohydrase activity of fecal bacteria and the level of microbial metabolites in the gastrointestinal tract of pigs1,2

Abstract: Two experiments with growing pigs were conducted to determine the effects of dietary P and Ca level, phytase supplementation, and ileal pectin infusion on ileal and fecal P and Ca balance, chemical composition of fecal mixed bacterial mass (MBM), and bacterial metabolic activity. Pigs (initial BW = 30 kg) were fitted with simple T-cannulas at the distal ileum. They were fed a low-P corn-soybean meal control diet (3 g of P/kg) or the control diet supplemented with monocalcium phosphate (MCP; 7 g of P/kg; Exp. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…Supplementation of a microbial phytase at 250, 500, or 1,000 FTU/kg did not influence stomach pH in 32kg pigs (Radcliffe et al, 1998), gastrointestinal pH in 42-d-old broilers (Nourmohammadi et al, 2011), or ileal pH in 21-d-old broilers (Akyurek et al, 2011). However, feeding 1,000 FTU/kg of phytase significantly increased fecal pH in 53-kg pigs (Metzler et al, 2008). The increase in gastric pH associated with high levels of supplemental phytase may be directly related to the breakdown of the phytate molecule by phytase.…”
Section: Discussionmentioning
confidence: 94%
“…Supplementation of a microbial phytase at 250, 500, or 1,000 FTU/kg did not influence stomach pH in 32kg pigs (Radcliffe et al, 1998), gastrointestinal pH in 42-d-old broilers (Nourmohammadi et al, 2011), or ileal pH in 21-d-old broilers (Akyurek et al, 2011). However, feeding 1,000 FTU/kg of phytase significantly increased fecal pH in 53-kg pigs (Metzler et al, 2008). The increase in gastric pH associated with high levels of supplemental phytase may be directly related to the breakdown of the phytate molecule by phytase.…”
Section: Discussionmentioning
confidence: 94%
“…Our results verified the speculation on the basis of AID of GE, in which diets containing 1,000 and 20,000 FTU/kg phytase contributed 548 kJ/kg and 1,922 kJ/kg as digested energy in the ileum, respectively. However, the lack of change in total tract energy digestibility may indicate that phytase supplementation depresses microbial fermentation in the lower intestine due to a possible deficiency of P and Ca (Metzler et al, 2008). Metzler et al (2010) reported that dietary phytase supplementation tended to reduce the concentration of total volatile fatty acids and the total number of bacteria in the feces.…”
Section: Discussionmentioning
confidence: 99%
“…Health was monitored daily and illness was determined by appetite, lethargy, behavior, and/or cannula function. Post-surgery, the skin around the cannula was cleaned with lukewarm water several times daily, treated with a skin-protecting paste (Stomahesive Paste, Convatec, Princeton, UK), and foam material was placed between the retaining ring and the skin to absorb leaking digesta to prevent erythema [21]. Pigs received new empty plastic water bottles as chewing material every day.…”
Section: Methodsmentioning
confidence: 99%